Relationship of The Economy and Investment Sector on The Implementation of Labor Central Sector of Central Java - Rifa Atun Mahmudah (Economics Development Analysis Journal, 2016)
This study aimed to analyze the linkages between sectors, multiplier and the investment sector’s role in increasing the amount of output and the amount of labor that can be absorbed in the economy in the Province of Central Java. This study used a quantitative approach with secondary data. The analytical tool used was the analysis of input-output tables Province of Central Java in 2013 primarily relies on domestic transactions table on the basis of producer prices. The results showed the role of economy based on the analysis forward linkages and backward linkages can be divided into leading sectors, growing sector, potential sectors and underdeveloped sector. Sectors with the highest output multiplier is the manufacturing sector. Sector with the highest labor multiplier is the agricultural sector. The results also showed that the leading sectors also have a growing sectors impact on the highest output and labor absorption of final demand investment, that is trade, hotels and restaurants; Manufacturing Industry; and agriculture. Increased investment will increase the value of output and an increase in output will increase employment. At last, investments have a positive relationship with employment.